Validity of dipstick urinalysis for predicting urinary tract infection in febrile children aged 2-12 years in a tertiary care centre, South Kerala - Cyril, Jose P.; Stephenson, Baburaj; Kuruvilla, Tinu Abraham; Devadas, Bobby Christy; Das, Lini B.; Baby, Suja (International Journal of Contemporary Pediatrics, 2021)
Background: Urinary tract infection (UTI) warrants an early accurate diagnosis in children. Use of rapid diagnostic tests like urine dipstick and microscopy was found to be economical and effective. There is lack of sufficient studies on rapid diagnostic tests in developing countries like India. This study looked at the single as well as combination of parameters that provided maximum sensitivity and specificity, providing a better diagnostic criterion in detecting UTI. The objective was to assess the diagnostic validity of urinary dipstick in the diagnosis of UTI in comparison with urinary culture. Methods: This cross-sectional diagnostic evaluation study was conducted in a tertiary care centre in Southern Kerala. Total of 75 children between the age group of 2 years to 12 years who attended the paediatric OPD with the clinical features of UTI were included in this study. Two urine samples were obtained in sterile containers. The first urine sample was assessed with dipstick and the second sample was sent for culture to confirm the UTI. The results obtained were analysed using SPSS software. Results: Using culture as gold standard, the results for nitrate alone had lower sensitivity at 69.69%, specificity at 90.4%. The results for LE (LE) alone had higher sensitivity at 81.8%, specificity at 80.95% and the results for combined urine dipstick had higher sensitivity at 84.8% than individual nitrite and LE. The combined positive predictive value (PPV) was lower than individual nitrite and LE 75.6%. The combined negative predictive value (NPV) was higher than individual LE and nitrite at 86.8%. Conclusions: Dipstick urinalysis alone may not be a completely adequate screening tool for UTI. Since urine dipstick test has high sensitivity it can be used as a bedside tool in detecting UTI in children.